Synergistic Effect Antibacterial Activity of The Combination of Andaliman (Zanthoxylum acanthopodium DC) Fruit Essential Oil and Erythromycin against Streptococcus mutans and Streptococcus pyogenes : Efek Sinergisme Aktivitas Antibakteri Kombinasi Minyak Atsiri Buah Andaliman (Zanthoxylum acanthopodium DC) dan Eritromisin terhadap Streptococcus mutans dan Streptococcus pyogenes - Situmorang, Vania Clarissha; Rahmi, Eldiza Puji; Pradana, Dhigna Luthfiyani Citra; Septama, Abdi Wira; Muti, Annisa Farida (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: The concept of synergism is one of the approaches taken to combat the problems related to antibiotic resistance. Objectives: The goal of this study was to determine the synergistic effect of the antibacterial activity of a combination of essential oil of Zanthoxylum acanthopodium DC fruit and erythromycin against Streptococcus mutans and Streptococcus pyogenes. Methods: The broth microdilution assay was used to determine the Minimum Inhibitory Concentration (MIC) of Z. acanthpodium DC fruit essential oil and erythromycin. The synergistic effects were assessed using the checkerboard method. Results: MIC value of Z. acanthopodium DC fruit essential oil against both bacteria was 2500 mg/mL. The combination of Z. acanthopodium DC fruit essential oil and erythromycin had a synergistic effect against S. mutans and S. pyogenes with fractional inhibitory concentration index (FICI) values of 0.375 and 0.0872, respectively. Conclusions: These results suggest that a combination of herbal plants and conventional antibiotics could be used as an alternative therapy for bacterial infections.